2022
DOI: 10.3390/polym14214548
|View full text |Cite
|
Sign up to set email alerts
|

Silica-Filled Polyacrylonitrile Solutions: Rheology, Morphology, Coagulation, and Fiber Spinning

Abstract: The fumed silica influence on the morphology, coagulation processes, and rheological properties of suspensions in dimethyl sulfoxide (DMSO) and polyacrylonitrile (PAN)–DMSO solutions has been studied for the production of composite films and fibers. It has been shown that silica–DMSO concentrated suspensions (24 wt%) form a weak gel with a yield point of about 200 Pa. At concentrations of ~5 wt% and above the dispersions, depending on the shear stress, are pseudoplastic or dilatant liquids. It has been found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…On the other hand, Ullah et al also reported good mechanical and thermal properties of PAN nanofibers, but the tensile strength decreased with the addition of silver sulfadiazine in PAN nanofibers during electrospinning [ 52 ]. When testing the strength of PAN fibers using a mechanotropic method, Varfolomeeva et al reported high-strength PAN fibers, but the addition of silica led to a decrease in fiber strength [ 53 ]. The addition of inorganic particles into a polymer matrix can improve the mechanical property of the membrane.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Ullah et al also reported good mechanical and thermal properties of PAN nanofibers, but the tensile strength decreased with the addition of silver sulfadiazine in PAN nanofibers during electrospinning [ 52 ]. When testing the strength of PAN fibers using a mechanotropic method, Varfolomeeva et al reported high-strength PAN fibers, but the addition of silica led to a decrease in fiber strength [ 53 ]. The addition of inorganic particles into a polymer matrix can improve the mechanical property of the membrane.…”
Section: Discussionmentioning
confidence: 99%
“…PAN solutions with TEOS additions were prepared at 70 • C on a laboratory opposing mixer [22], which allows homogenizing concentrated polymer solutions, protecting them from ingress of air and moisture from the outside.…”
Section: Spinning Solution Preparationmentioning
confidence: 99%
“…SiO 2 is used as a silicon-containing modifier component, and composite fibers obtained by electrospinning [7,14,[18][19][20][21], often, simultaneously with achieving the required special characteristics demonstrate inhomogeneous morphology due to the formation of large aggregates [7,8,12,14,20], that could decrease mechanical properties [12,22].…”
Section: Introductionmentioning
confidence: 99%